“Eis que tudo se fez (quase) novo”: sobre a conversão de ex-prostitutas - Ferreira, Nilton César (2019)
The research presented here is the result of reflections on the functioning of a Pentecostal discourse of Brazilian Christianity which strongly links the social rehabilitation of marginalized subjects, especially women who once prostitute themselves, to a soteriological proposal of religious conversion. The analysis of linguistic materiality allows the understanding of the meanings derived from the inscription of the language in history. In this discursive process, one can deduce that ideology is what produces a naturalization of the senses, placing man in the imaginary relation with his material conditions of existence, in order not only to affect the subject, but to mold it. The corpus of this research is based on interviews with certain subjects of the Evangelical Church Assembly of God, specifically the Belém Ministry, among them, an evangelical pastor, a representative of the group of ladies and two ex-prostitutes converted to the Pentecostal religion. With this regard, the present research appears as a fruitful opportunity to verify how the Christian-Pentecostal subjects validate the experience of religious conversion. The interviews are analyzed as a discursive approach, seeking to understand how such an evangelical denomination arise as an ideological apparatuses, insofar as those discourses link the abandonment of female prostitution to religious experience. The choice by the theoretical contribution of the Discourse Analysis of French orientation aims to investigate the order of the statements, which allows a reflection on the crystallized senses present in the discourse of certain Christian subjects. As a result of this process of investigation, we understand that prostitution is seen as morally reprehensible in the West. We also observed that, although the conversion proposal is presented as more effective regarding re-socialization of marginalized subjects, this discourse fails in relation to women who once practiced prostitution, given the social stigma they suffer.